2014
DOI: 10.1111/cote.12086
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dye chemical structure on adsorption on activated carbon: a comparative study

Abstract: The effect of the molecular structure of dyes Eriochrome Black T and Bromophenol Blue on their adsorption on the surface of activated carbon manufactured from locally available biosorbent has been studied. Batch experiments were performed to investigate factors that may affect the adsorption process. The effect of stirring rate was investigated in the range 0–240 rpm, with an initial concentration of 4–100 mg/l and a stirring time of 0–400 min. The mechanism and rate of adsorption were investigated for both dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 26 publications
4
27
0
Order By: Relevance
“…The adsorption capacity of LCAC, however, increased continuously from 96.1 to 178.6 mg/g for AO and 79.5 to 132.5 mg/g for AzB with increasing initial dye concentrations. Similar result has been reported for the adsorption of bromophenol blue onto activated carbon (Altaher et al 2014), which has been explained on the basis that higher dyes concentration acted as an increased driving force for the adsorption. The optimum initial dyes concentration was 80 mg/L.…”
Section: Effect Of Initial Dyes Concentrationsupporting
confidence: 87%
“…The adsorption capacity of LCAC, however, increased continuously from 96.1 to 178.6 mg/g for AO and 79.5 to 132.5 mg/g for AzB with increasing initial dye concentrations. Similar result has been reported for the adsorption of bromophenol blue onto activated carbon (Altaher et al 2014), which has been explained on the basis that higher dyes concentration acted as an increased driving force for the adsorption. The optimum initial dyes concentration was 80 mg/L.…”
Section: Effect Of Initial Dyes Concentrationsupporting
confidence: 87%
“…So, the most important steps are film diffusion, pore diffusion and chemical reaction. Therefore, adsorption diffusion models are mainly constructed to describe the process of film diffusion and/or intra-particle diffusion because the pseudo-first-order and pseudo-second-order models cannot identify the diffusion mechanism [42,43]. Weber and Morris [34] described the intra-particle uptake of the adsorption process to be proportional to the half-power of time.…”
Section: Biosorption Kineticsmentioning
confidence: 99%
“…Scanning electron microscopy (SEM) has been a primary tool for characterizing the surface morphology and fundamental physical properties of the adsorbent surface. It is useful for determining the particle shape, porosity and appropriate size distribution of the adsorbent [21,42,48]. The morphological profile of the biosorbent revealed a rough and heterogeneous surface with relatively porous matrix of macroporous character, pointing towards its potential in taking up the dye.…”
Section: Sem Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported on different treatments such as degradation (Soutsas et al, 2010), coagulation (Beltrán-Heredia, Sánchez-Martín, Delgado-Regalado, & Jurado-Bustos, 2009), ultrafiltration through membranes (Simoni c, 2009), and adsorption (Bhatt et al, 2012;Kallel et al, 2016;Liu et al, 2009;Melo et al, 2017) for dye removal. The adsorption process is commonly used in industry because of its simple operation, high efficiency, and cost effectiveness with good potential for reuse and recovery (Altaher, Khalil, & Abubeah, 2014;Dallago, Smaniotto, & Oliveira, 2005). Studies have reported that highly functional porous materials act as suitable adsorbents due to the existence of polar and nonpolar groups in their chemical structures that impart effective and excellent chemical as well as thermal resistance properties (Sanghi & Bhattacharya, 2002;Shirke, Dholakiya, & Kuperkar, 2015).…”
Section: Introductionmentioning
confidence: 99%